Resource allocation in heterogeneous networks using game theory - Yuan, Pu (2015)
The proposed infrastructure of the next generation wireless networks not only contains the centralized control but also enables the mobile devices to make distributed decisions. The focus of this thesis is to investigate the application of game theoretic approaches in distributed solutions to resource allocation problems in wireless networks. As a useful analytical tool to find distributed solutions to various practical problems, game theory has great potential to be applied in modeling various wireless communication problems, such as spectrum allocation, interference management, accessing mode selection, etc.. Furthermore, it gives us an insight into the behavior and interaction among the independent autonomous mobile nodes. Our work reported in this thesis is focused on two emerging fields in wireless network research: the spectrum-sharing based heterogeneous networks (HetNets) and the device-to-device communication enabled mobile networks. The former has been included in the Long Term Revolution Advanced (LTE-A) standard as a promising technique in enhancing the network capacity. The latter is considered to be a competitive technique to further improve the quality of service (QoS) and latency in the mobile network. Geared with the game theoretic tools, we investigate some fundamental problems in the spectrum-sharing based heterogeneous networks, and provide practical and distributed algorithms to solve a series of resource allocation problems.